Scarf Osteotomy without Internal Fixation for Hallux Valgus: A Systematic Review - Adrian JC Tablante; Emiliano B Tablante (Journal of Foot and Ankle Surgery (Asia Pacific))
Background: Scarf osteotomy is traditionally performed with screw fixation and has been found to be useful for moderate to severe grade deformities. Our study aimed to evaluate the efficacy and safety of scarf osteotomy without internal fixation for hallux valgus deformity correction based on the available literature. Methods: A systematic search of PubMed and the Cochrane database of controlled trials was performed to include any available studies that examine the effectiveness of scarf osteotomy without internal fixation in terms of clinical or radiographic outcomes, as well as complications. The methodological quality of each study was assessed using the MINORS criteria. Results: Five studies were included in this systematic review (four cases series and one retrospective comparative study). We noted that all studies concluded acceptable outcomes using scarf osteotomy without internal fixation with the American Orthopaedic Foot and Ankle Society (AOFAS) score improving from an average of 46.5–91, the mean hallux valgus angle improving from 32.9° to 9.7°, the mean intermetatarsal angle improving from 14.5° to 6.1°, and lastly, the mean distal metatarsal articular angle from 15.5° to 5.9°. Complication rates were low across all studies with a 5.5% in 305 patients, with displacement being the most common complication accounting for 2.2% across all studies. Conclusion: Scarf osteotomy without internal fixation has been shown to have potential in the treatment of hallux valgus deformities. Acceptable results and complication rates suggest that this technique can be a viable alternative for patients, especially those who are financially burdened and those who cannot afford increased hospital time. However, there is limited knowledge and small number of research studies on this surgical technique. The current systematic review hopes to invoked renewed interest in this technique. Clinical significance: Scarf osteotomy without internal fixation can provide a cheaper alternative to the standard protocol of hallux valgus correction as it does not need an implant for internal fixation and can theoretically provide comparable results which can lessen the financial burden for patients such as those living in third-world countries.